Student perceptions of model-based estimating. Issue 2 (3rd April 2019) - Elliott, Jonathan W.; Glick, Scott; Valdes-Vasquez, Rodolfo
ABSTRACT: The use of building information modeling (BIM) is well established in architecture, engineering and construction. However, previous studies note a lack of BIM expertise in academia, leading to slow adoption and limited knowledge on which to base BIM-related content. To improve course development, it is important to understand students' perceptions of BIM-related subject matter. This study exposed estimating students ( n = 214) to a model-based quantity takeoff (QTO) tutorial using Revit. Students' perceptions of a Revit-based BIM's usefulness for easily providing reliable and accurate material quantities were measured using a pre-test, tutorial and post-test design. Results revealed significant differences in students' mean levels of agreement that an accurate QTO is completed for an estimator with the click of a button when a design team generated BIM model is available. Results also revealed significant differences in students' level of agreement that a Revit-based BIM makes performing QTO by hand obsolete. This study provides educators' insight into students' perceptions of BIM use in QTO. Understanding student perceptions is paramount for construction management educators when designing a course and attempting to convey the value of foundational estimating skills while acknowledging the existence of more technologically advance estimating methods. Limitations and opportunities for further research are discussed.